PENGARUH EDUKASI MENGGUNAKAN MEDIA LEMBAR BALIK TENTANG TUBERKULOSIS TERHADAP PENGETAHUAN DAN SIKAP PADA KELUARGA PASIEN DI WILAYAH KERJA PUSKESMAS NANGKAAN BONDOWOSO - Hasanah, Uswatun; Rachman, Moh. Zainol; Wahyuni, Tavip Dwi; Wandi, Wandi (Poltekkes Kemenkes Malang, 2024)
Tuberculosis (TB) is an infectious disease that attacks the lung parenchyma caused by Mycobacterium Tuberculosis. The purpose of the study was to determine the effect of the flip sheet media about tuberculosis on the knowledge and attitudes of the patient's family in the working area of the Nangkaan Bondowoso Health Center. This type of research used quantitative research with Pre-experimental research design one group pre test and post test design. The population in this study were patient families from the Nangkaan Health Center work area as many as 30 respondents using total sampling. Data collection techniques during the study were obtained when conducting education, namely by filling out pre-test and post-test questionnaires. Based on the results of hypothesis testing, it is known that there is an influence of the flip sheet education media on efforts to increase knowledge and attitudes in the families of tuberculosis patients, this is seen through the level of significance obtained p-value = 0.000, thus this study rejects Ho, meaning that there is an influence of media in increasing knowledge and attitudes, it is known that there is an increase of 29% in the level of knowledge and it is known that there is an increase of 6% in the attitude of the families of tuberculosis patients who have been given education through the flip sheet media..